Environmental technology development in liberal and coordinated market economies : tweaking institutions - Wong, Shiu-Fai (Palgrave Macmillan, 2006)
This book explores the role of institutions in policy-making and the states? role in promotion of technology, focusing on environmental technology development. Case studies include wind power diffusion in the UK and Germany, waste recycling in a variety of countries, and green automobile technology in the US and Japan.